St. Mary's church, Killyleigh, north chancel wall, aumbry jamb and arch - O'Donovan, Danielle (My University, 2008)
Jamb and arch moulding of aumbry, moulding comprises: ogee with convex surface at corner and concave surface running along outer face.
Aumbry
Keywords: Architecture, Gothic -- Ireland; Down, Ire. (County); Late Medieval; moldings, ogee